6‐ shogaol suppresses AOM/DSS‐mediated colorectal adenoma through its antioxidant and anti‐inflammatory effects in mice. Issue 12 (20th September 2022) - Ajeigbe, Olufunke Florence; Maruf, Opeyemi Rabiat; Anyebe, Daniel Abu; Opafunso, Ifeoluwa Tobi; Ajayi, Babajide Oluwaseun; Farombi, Ebenezer Olatunde
Abstract: Colorectal adenoma appears as benign lesions and is a precursor of colorectal adenocarcinoma. The effect of 6‐Shogaol (6‐[S]), a bioactive agent from ginger, in early colonic adenoma growth is unknown. As a result, this study examines the effect of 6‐[S] in a mouse colorectal adenoma model induced by Azoxymethane (AOM) and dextran sulfate sodium (DSS). Adult male mice served as control in Group 1. Group 2 was treated orally with 6‐[S] extract (20 mg/kg BW). Group 3 was exposed to AOM (25 mg/kg BW, ip) and one cycle of DSS (2.5%) in drinking water alone while Group 4 was co‐treated with 6‐[S] for twenty‐one (21) days. The body weight gain, organ weight and length, oxidative stress indices, inflammatory markers and histological examination were estimated. Our findings show that 6‐[S] co‐treatment reversed AOM/DSS‐induced elevation in colon weight, colon length, nitric oxide (NO), myeloperoxidase (MPO), hydrogen peroxidase (H2 O2 ), and tumor necrosis factor‐alpha (TNF‐α). However, the antioxidant enzyme activities measured namely catalase (CAT), superoxide dismutase (SOD), reduced glutathione (GSH), and glutathione‐S‐transferase were significantly increased in 6‐[S] treated mice. Taken together, the protective effect of 6‐[S] on oxidative burden, inflammation, and histological aberration observed in the colon of the AOM/DSS model of adenoma growth in mice is mediated primarily owing to its anti‐inflammatory and anti‐oxidative properties. Thus, this study reveals 6‐[S] as a useful agent in the possible clinical intervention of colorectal adenoma. Practical applications: Certain spices have been reported to have numerous phytochemicals with numerous medicinal purposes. However, no studies have been conducted to investigate the role of 6‐[S], a phytochemical found in ginger, in the treatment of colorectal adenoma. The study's findings show that 6‐[S] is protective in early colonic cancer development, as it manages colorectal adenoma cancer models of AOM/DSS. As a result, 6‐[S]'s ability to reduce oxidative stress and inflammation in the colon may be a potential nutritional therapeutic adjuvant for colorectal adenoma. Abstract : This paper reported the chemoprotective effect of 6‐ Shogaol, 6‐[S] derived from ginger extract on azoxymethane (AOM) and dextran sulphate sodium (DSS)‐induced colorectal adenoma in mice. Treatment with 6‐[S] prevented tubular adenoma and dysplasia in the colon of AOM/DSS treated Mice. 6S prevented colonic oxidative stress in AOM/DSS treated mice as well as colonic inflammation in AOM/DSS treated mice.